Hilangnya Kesadaran Palsu: Sakralisasi Mesjid sebagai Simbol Pergerakan Roda Ekonomi Masyarakat Miskin di Pedesaan (Studi Kasus Masyarakat Kampung Kukupu Kelurahan Cibadak Kec.Tanah Sareal) - ; Yogaprasta A Nugraha (Universitas Pakuan, 2018)
AbstractDiscourse about how far religions are able to develop and destroy a society still worth to discuss. Different type of study between west and east (Islamic State) producing different conclusion. The fundamental different is located in the role of religion to society, in west area, there is still no evidence that religion can give any benefit toward societies life, meanwhile in east life there is evidence that religion can contribute positively toward societies life. These two differents type of conclusion become important assets in studying contemporary social-religion phonemenon. This kind of discussion is important considering the rise of society awareness about the importance of religion in solving problem.Keywords: masjid, social-religion phenomenon